Click Addition of a DNA Thread to the N-termini of Peptides for Their Translocation through Solid-State Nanopores - Biswas, Sudipta (ACS Nano, 2015)
Foremost among the challenges facing single molecule sequencing of proteins by nanopores is the lack of a universal method for driving proteins or peptides into nanopores. In contrast to nucleic acids, the backbones of which are uniformly negatively charged nucleotides, proteins carry positive, negative and neutral side chains that are randomly distributed. Recombinant proteins carrying a negatively charged oligonucleotide or polypeptide at the Ctermini can be translocated through a α-hemolysin (α-HL) nanopore, but the required genetic engineering limits the generality of these approaches. In this present study, we have developed a chemical approach for addition of a charged oligomer to peptides so that they can be translocated through nanopores. As an example, an oligonucleotide PolyT(20) was tethered to peptides through first selectively functionalizing their N-termini with azide followed by a click reaction. The data show that the peptide-PolyT(20) conjugates translocated through nanopores whereas the unmodified peptides did not. Surprisingly, the conjugates with their peptides tethered at the 5′-end of PolyT(20) passed the nanopores more rapidly than the PolyT(20) alone. The PolyT(20) also yielded a wider distribution of blockade currents. The same broad distribution was found for a conjugate with its peptide tethered at the 3′-end of PolyT(20), suggesting that the larger blockades (and longer translocation times) are associated with events in which the 5′-end of the PolyT(20) enters the pore first.